Assessment of Knowledge, Attitude and Practice on Biomedical Waste Management Among Healthcare Workers at Approved Covid Testing Sites in Jamaica - Pitkin, Fabian; Brown, Gillian; Lewis, Danielle; Jacobs, Sabrina; Wray , Chantal; Benjamin, Chrissanna; Williams, Abigail (European Journal of Applied Sciences, 2023)
For most developing countries the onset of the Covid -19 pandemic increased the need for testing and subsequently, an increased in approved testing sites. Most sites during the height of the pandemic, handled large quantities of biomedical waste. Like all other biomedical wastes, those generated from the testing of Covid-19 patients, pose a significant risk for infection and injury when they are improperly handled. Such infections can easily spread among healthcare personnel, patients, visitors, and the wider society. This research aimed at highlighting the importance of proper biological waste management (BWM) and investigating the knowledge, attitude, and practice of healthcare workers as it relates BWM at approved covid testing site in Jamaica. Healthcare workers at these testing sites are first contact with infected patients and the resultant biomedical waste generated during the testing process, as such their knowledge, attitude, and practices with regards to appropriate BWM is crucial in understanding areas of potential spread of the deadly infection. A cross-sectional study was carried out in which a valid three step self-reporting questionnaire was designed through a review of literature and was distributed among 60 randomly selected healthcare workers at approved sites across the island. The findings revealed that most (86.7%) HW had excellent knowledge of proper biomedical waste management. In relation to their attitude, most of the respondents (91.7%) indicated that the guidelines were necessary for their own safety as well as for others. With respect to practices, majority (98.3%) of the HWs indicated that they were compliant with the established standards for biomedical waste management. Overall, training appears to be the major determinant of knowledge, attitude, and practice among the participants.